2006
DOI: 10.2223/jped.1437
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal colonization with Streptococcus pneumoniae in children infected with human immunodeficiency virus

Abstract: Objectives: To determine the prevalence of pneumococcus colonization among HIV-infected outpatients aged 0 to 18 years. To determine the resistance to penicillin of the microorganisms observed, to identify their serotypes, and to determine whether there are associations between known risk factors and colonization in this group. Material and method:This was an observational and crosssectional study in which nasopharynx swabs were collected from 112 children on the occasion of their monthly appointments and a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
3
12
1
Order By: Relevance
“…No information on nasopharyngeal carriage rates with Hib in children with HIV was found. The prevalence of pneumococcal colonization of 28% is comparable to studies of Brazilian and Romanian children with HIV [18,19].…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…No information on nasopharyngeal carriage rates with Hib in children with HIV was found. The prevalence of pneumococcal colonization of 28% is comparable to studies of Brazilian and Romanian children with HIV [18,19].…”
Section: Discussionsupporting
confidence: 64%
“…ART did not prevent nasopharyngeal colonization with Hib or pneumococcus. Similarly, a study of Brazilian children with HIV also showed no association between pneumococcal colonization and ART use [19]. There is limited information on the effect of ART on Hib disease or Hib colonization, because only a few countries remain with a significant burden of pediatric HIV who are yet to adopt the Hib conjugate vaccine into immunization programs [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These serotypes accounted for 59% of serotypes recovered from HIV-positive mothers, compared with 37% of serotypes recovered from HIVnegative mothers (RR, 1.5; 95% CI, 0.96 -2.4). Serotypes 7,8,9,10,11,14, and 33 occurred predominantly or exclusively among HIV-positive mothers (RR, 1.8; 95% CI, 0.7-5.0). Among the dominant serotypes, the predominant sero/factor types were 6b, 19f, and 23f.…”
Section: Resultsmentioning
confidence: 99%
“…Nasopharyngeal and/or oropharyngeal colonization with S. pneumoniae is considered a precondition for invasive pneumococcal disease [8,9]. Whether HIV infection increases the risk of nasopharyngeal colonization in children and adults is unclear [10,11]. Recent studies suggest that HIV-positive adults tend to be colonized by pneumococcal serotypes more commonly seen in children [12][13][14].…”
mentioning
confidence: 99%